Current potential of more sustainable biomass production using eco-efficient farming practices in Austria. (1st July 2017) - Maier, Stephan; Szerencsits, Manfred; Narodoslawsky, Michael; Ismail, Iqbal Mohammad Ibrahim; Shahzad, Khurram
Abstract: Ecological evaluation approaches assess different levels of comprehensiveness depending on anthropogenic ecological pressures on natural material and biogeochemical cycles. In this research potentials of biomass integration in agricultural processes were evaluated and all parts of their full life cycles were replaced with ecological processes of low impact. A method that covers global resource availabilities, life cycle chains and their emissions to final compartments on earth' spheres in a detailed way is Sustainable Process Index. This footprint calculator accumulates the total resource use of a full life cycle of a process chain in one number of m 2 area. Current typical conventional agricultural cropping processes shall be made comparable to a strongly sustainable ecological footprint which could be achieved if heavy footprint measures would be replaced by those with smaller impacts in natural cycles. The production of maize grain is evaluated to find out the ecological hotspots. A comparison of business as usual conventional farming practice and ecological/organic farming practice is carried out. The evaluation results confirmed that fossil fuel consumption and application of mineral fertilizers along with pesticides are the main ecological hotspots. The ecological footprint and carbon footprint showed a bandwidth of 24, 731 to 10, 690 m 2 /tonne and 88.5 and 22.6 kg carbon dioxide equivalent per tonne maize grain production respectively. The shift from conventional farming practice to organic farming and use of biogas as fuel showed an ecological footprint reduction potential ranging from 22% to 57% while the carbon footprint reduction potential ranges from 38% to 74%. It proves that SPI footprint methodology is quite effective in locating ecological hotspots and finding alternate environment friendly solution in the life cycle of a process. The assessment results are very promising and indicate that a shift from conventional farming practices towards organic farming and the use of renewable energy sources have a huge potential to achieve a more sustainable agriculture and strengthen a regionally based economy. Highlights: Ecological hotspots in agri-sector are use of mineral fertilizers and fossil fuel. Organic farming has lower environmental pressure than conventional one. Change of diesel fuel with biogas reduces ecological impact of farming practice. Ecological footprint varies from 24, 731 to 10, 690 m 2 /t corn production. Carbon footprint changes from 88.5 to 22.6 kg CO2 equiv./t corn production.